Top 7,000 & next 5,000 corporations the engines of economic growth business profiles 2003-2004. - Philippine Business Profiles and Perspectives, Inc. (Pasig City Philippine Business Profiles and Perspectives, 2004)
This CD-ROM contains a database of top 12,000 corporations from 2001 to 2002, list of industry standards and company profiles. Articles and past databases of top 12,000 corporations are also included.
Articles -- Database of top 12,000 '01-'02 -- List of industry classification '01-'02 -- Company profiles '01-'02 -- Historical database top 12,000 '00, '99, '98, '97, '96.
System requirements: Pentium 133 Mhz or higher; 32MB RAM (64MB or higher recommended); Windows 95 & up; 12x CD-ROM drive; 640x480 resolution: 16 bit color or higher monitor.
Keywords: Corporations -- Philippines